2018
DOI: 10.2135/cropsci2017.08.0497
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Stability of Carbohydrate Profiles in Different Soybean Genotypes

Abstract: Soybean [Glycine max (L.) Merr.] is an important annual crop. The raffinose family oligosaccharides (RFOs) raffinose and stachyose are antinutritional carbohydrates present in soybean seeds. Consumption of soybean seed products with low RFO reduced flatulence in humans and increased metabolizable energy efficiency in chickens, pigs, and dogs. The development of soybean cultivars producing high metabolizable energy with low antinutritional factors in the seed is one avenue to increase soybean value. The soybean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 22 publications
(41 reference statements)
4
25
1
Order By: Relevance
“…This is consistent with the results reported by Cicek et al (2006) using a population of 303 RILs derived from an interspecific cross. These PIs have not been previously reported to possess such specific sugar features, and no genetic connection between them and previously reported lines has been evidenced by molecular marker and/or pedigree information (Hou et al, 2009;Jo et al, 2018). In the present study, no germplasm accession with that high of glucose and/or fructose content was found.…”
Section: Methodscontrasting
confidence: 64%
See 1 more Smart Citation
“…This is consistent with the results reported by Cicek et al (2006) using a population of 303 RILs derived from an interspecific cross. These PIs have not been previously reported to possess such specific sugar features, and no genetic connection between them and previously reported lines has been evidenced by molecular marker and/or pedigree information (Hou et al, 2009;Jo et al, 2018). In the present study, no germplasm accession with that high of glucose and/or fructose content was found.…”
Section: Methodscontrasting
confidence: 64%
“…These lines include five low-raffinose PIs (PI 603443B, PI 358323, PI 603426E, PI 603429A, and PI 612753A; raffinose content < 3 mg g −1 ), one high-sucrose PI (PI 291329; sucrose content > 64 mg g −1 ), 15 PIs with >120 mg g −1 in total sugar content, and four PIs high in both sucrose and total sugar (PI 538395, PI 458827, PI 597651, and PI 597652). These PIs have not been previously reported to possess such specific sugar features, and no genetic connection between them and previously reported lines has been evidenced by molecular marker and/or pedigree information (Hou et al, 2009;Jo et al, 2018). We also confirmed seven high-protein PIs (PI 468909, PI 612758A, PI 468910, PI 319536B, PI 612759B, PI 603712, and PI 597467) with an average of >462 mg g −1 over three environments, in spite of being coupled with a lower oil concentration (130.9-178.9 mg g −1 ).…”
Section: Methodsmentioning
confidence: 75%
“…Previous studies have investigated the stability of soluble carbohydrate profiles of soybean lines having different combinations of RS2 and RS3 alleles with different environmental conditions such as a planting date study, a location study, and a year study in Missouri (Hagely et al, 2013; Bilyeu and Wiebold, 2016; Jo et al, 2018). The current research was to extend the understanding of environmental stability of carbohydrate profiles in soybean seed in multiple soybean production areas in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…Both of these rs2 mutants have reduced levels of raffinose (0.1-0.2% raffinose as a percentage of total seed carbohydrates) relative to lines wild type for RS2 (0.8-1% raffinose) in replicated field tests [8]. Stachyose levels are also reduced in the rs2 single mutant (0.5-2% of total seed carbohydrates) contrasted with 4% of total carbohydrate in wild type lines, and moderate increases in total sucrose levels [8,9]. A biotechnological approach silencing the RS2 gene in soybean seeds also achieved significant reductions in seed RFOs and an increase in sucrose [4].…”
Section: Introductionmentioning
confidence: 99%
“…A biotechnological approach silencing the RS2 gene in soybean seeds also achieved significant reductions in seed RFOs and an increase in sucrose [4]. Mutation in RAFFINOSE SYNTHASE3 has been shown to reduce RFOs further when combined with a non-functional allele of rs2, resulting in ultra-low levels of raffinose and stachyose of less than 2% as a fraction of total seed carbohydrates [8][9][10][11]. While the decrease in RFO content is desirable for meal digestibility, the alteration of carbohydrate partitioning resulting in increased levels of sucrose, which contributes to the metabolizable energy in soybean meal is an added advantage [12,13].…”
Section: Introductionmentioning
confidence: 99%